Comparing Regional Organizations : Global Dynamics and Regional Particularities - Panke, Diana; Starkmann, Anna; Stapel, Sören (Book collections on Project MUSE., 2020)
This book provides a valuable overview of the evolution and particularities of regional organizations across Africa, the Americas, Asia and Europe since 1945. The authors analyze the membership dynamics and policy scopes of 76 organizations, and compare their opportunities and challenges in regional governance. They consider organizations' competencies in a variety of policy areas, including trade, security, environment, good governance and more, and trace patterns in their development. For those with interests in international relations and international law, political science and comparative regionalism, this is an essential companion to the work of some of the world's most significant organizations.This book provides a valuable overview of the evolution and particularities of regional organizations across Africa, the Americas, Asia and Europe since 1945. The authors analyze the membership dynamics and policy scopes of 76 organizations, and compare their opportunities and challenges in regional governance. They consider organizations' competencies in a variety of policy areas, including trade, security, environment, good governance and more, and trace patterns in their development. For those with interests in international relations and international law, political science and comparative regionalism, this is an essential companion to the work of some of the world's most significant organizations.--